Structure of codes over the ring - Bayram, Aysegul; Siap, Irfan (SPRINGER, 2013)
In this paper, we study the structure of linear codes over the non chain ring . In order to study the codes, we first study the structure of this ring via a distance preserving Gray map which also induces a relation between codes over this ring and ternary codes. Further, the algebraic structure of cyclic and dual codes is also studied. A MacWilliams type Identity between the Gray weight enumerators of the original code and its dual is established. In all cases examples that illustrate the theorems and lemmas are provided. Also, a BCH-type bound and an example that attains this bound is presented.
Keywords: Non chain ring; Linear codes; Cyclic codes; MacWilliams identity; BCH-type bound; SELF-DUAL CODES; RESPECT; Computer Science; Mathematics